Utilisation of non-steroidal anti-inflammatory drugs (NSAIDs) through community pharmacies in Malaysia - Chua, Siew Siang; Paraidathathu, T. (SAGE Publications, 2005)
This study was conducted to evaluate the use of non-steroidal anti-inflammatory drugs (NSAIDs) by consumers who obtained these drugs from community pharmacies. Factors that influenced community pharmacists in their choice of NSAIDs were also determined. Personal interviews were conducted on consumers who visited the 25 participating community pharmacies throughout Malaysia. Of the 389 respondents, 49 requested for an NSAID by name, 42 asked the pharmacist to recommend a medication and 9 had a doctor's prescription. NSAIDs were mainly purchased for joint/shoulder pain and the most commonly dispensed was diclofenac. Elderly respondents were more likely to be dispensed a selective COX-2 inhibitor than those below 60. NSAIDs were recommended based mainly on the pharmacist's perception of their efficacy, cost and safety. Community pharmacists play an important role in assisting patients in choosing the most appropriate NSAID for their health problems.